Assessment of System Accuracy, Intermediate Measurement Precision, and Measurement Repeatability of a Blood Glucose Monitoring System Based on ISO 15197. (March 2019) - Jendrike, Nina; Baumstark, Annette; Pleus, Stefan; Mende, Jochen; Haug, Cornelia; Freckmann, Guido
Background: Analytical quality of blood glucose monitoring systems (BGMS) is an important aspect for many diabetes patients. Sufficiently high analytical quality is required for adequate diabetes therapy. Methods: In this study, system accuracy and measurement precision of a BGMS were assessed based on ISO 15197:2013. For system accuracy, this standard requires a specific glucose distribution and at least 95% of results obtained with the BGMS in capillary blood to fall within ±15 mg/dl or ±15% (at glucose concentrations <100 mg/dl or ≥100 mg/dl, respectively) of corresponding comparison method results, and at least 99% of results to be found within clinically acceptable consensus error grid (CEG) zones A and B. Based on ISO 15197:2013, intermediate measurement precision, using control solution, and measurement repeatability, using venous blood samples, were analyzed by calculation of standard deviations (SDs) and coefficients of variation (CV) at glucose concentrations <100 mg/dl or ≥100 mg/dl, respectively, although ISO 15197:2013 does not specify acceptance criteria. Results: The BGMS fulfilled system accuracy requirements with ≥99% of results within ±15 mg/dl or ±15% of the comparison method results, and 100% of results in CEG zones A and B. Intermediate measurement precision analysis showed SD ≤2.2 mg/dl and CV ≤2.3%. Analysis of measurement repeatability showed SD ≤2.1 mg/dl and CV ≤2.4%. Conclusion: System accuracy requirements of ISO 15197:2013 were fulfilled by the BGMS. As ISO 15197:2013 does not specify precision requirements, precision analysis results were compared with those reported for other BGMS in the literature and found to be similar.